(3GdGbJUGO GdLRFj (B1 : s (3OQhS h JeGQjf eMdhdI (B: (3eWHhYI ehLgI dWdHI GdSfI GdGhdi LPY eTJQc (B/ s - (3NWGQ, hgjHIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3ebOeI aj GdJMdjd GdGbJUGOj, fXQjI GdWdH, fXQjI GdYQV, eQhfI GdWdH h GdYQV, JhGRf GdShb, JMdjd Sdhc GdeSJgdc(B( (3fXQjI GdeSJgdc(B).s
(3eQGLY U(B.140s
Keywords: (3GdGbJUGO GdLRFjs